The Concept of Understanding Impurity among LDII West Nias in a Review of Hadith - Nazih Mar’ie Zebua; Sugeng Wanto; Fadhilah Fadhilah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to determine the understanding of najis among LDII members and to identify the practice of Hadith regarding Najis among the Indonesian Islamic Propagation Institute of West Nias. The method used in this study is qualitative with a case study approach. The results of the study show that (1) the concept of najis in LDII is the same as that taught in Islam, which refers to something that is dirty and must be cleaned, in accordance with religious teachings that emphasize the importance of maintaining cleanliness, both physically and spiritually. Allah SWT loves His servants who protect themselves from impurity, whether it be major or minor impurity. (2) In practice, members of the Indonesian Islamic Propagation Institute of West Nias always prioritize personal hygiene and the cleanliness of places of worship in accordance with Islamic teachings. This is especially true in understanding and practicing the verses of the Qur'an and the hadiths. In fact, this is taught to preschool children. This is done solely to instill an understanding of the dangers of impurity in the minds of the next generation of the Indonesian Islamic Da'wah Institute from an early age